Peranan Kekuatan Alat Bukti Keterangan Ahli dan Visum Et Revertum dalam Tindak Pidana Pembunuhan Anak oleh Ibunya di Wilayah Hukum Polda Bali - I Nyoman Sukerta; Luh Nila Winarni; Cokorde Istri Dian Laksmi Dewi (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The strength of the evidence of the Expert Testament and the Visum Et Revertum that was submitted as a judge's consideration in deciding the crime of the murder of a child by his mother at the Bali Regional Police. The research method used is Empirical Juridical Research. Method: The research specifications are used through library research, the source of legal material used is primary legal material and secondary legal material, the approach used is the case approach. The technique of collecting legal materials used in this study is through interviews, observation and documentation. Result: Based on the results of research conducted by the author in the results obtained that the strength of the evidence Expert Testament and Visum Et Revertum in criminal cases are considered as legal evidence and have the strength of evidence but must be associated with the book ain so as to create a material truth. The judge in issuing a decision has obtained confidence based on a minimum of two valid evidences, the Judge also uses Visum Et Revertum as a material for consideration and assesses that there is a supporting link between the results of the examination of the Visum Et Revertum examination with the Criminal Act conducted so that the judge declares that the defendant is proven guilty commits a crime and is convicted of a criminal sentence.